Grain size effect of Ni–W–Cu seed layer film upon signal-to-noise ratio for PMR application. (October 2015) - Chen, Kun-Ming; Cheng, Yun-Kai; Liao, Hao-Chia; Chen, In-Gann; Hwang, Weng-Sing
Abstract: This study investigated the effects of W and Cu on the microstructure of Ni–W–Cu films which are used as the seed layer in perpendicular magnetic recording (PMR) media. Attributed to the relatively large radius of W, (i) the lattice mismatch between the seed layer and the intermediate layer in PMR, and (ii) the grain refining were successfully improved, in the presence of x increased in Ni80−x Wx Cu20 (x = 8, 14, 20). In addition, the decayed crystallinity resulting from increasing x value was ameliorated by raising y in Ni92−y W8 Cuy (y = 0, 10, 20). It is believed that the reduced grain size and the enhanced crystallinity are beneficial to signal-to-noise ratio (SNR) in PMR media. Furthermore, both the adhesion and the sputtering-arcing tests passed the industrial standards. All the results were supported by glancing incident X-ray diffraction (GIXRD), transmission electron microscopy (TEM), and spatial energy dispersive spectroscopy (EDS). Highlights: With increasing x, the lattice mismatch of Ru/Ni80−x Wx Cu20 was diminished from 8.1% to 6.0%. Given W tending to segregate on grain boundaries, grain size decreased with x in Ni80−x Wx Cu20. Amorphism occurrence was improved via adding Cu in Ni92−y W8 Cuy .